Hybrid rice for tomorrow's food security: can the Chinese miracle be replicated in other countries? - Janaiah, A.; Hossain, Mahabub; Husain, Muazzam (SAGE Publications, 2002)
The growth in rice production in Asia fell from 2.6% between 1966 and 1990 to 1.4% during the 1990s, mainly due to a deceleration in yield growth in the most intensively irrigated environments, where farm-level yields had already reached about 6.0 t ha–1. At this threshold of yields, farmers required more groundbreaking technology to elevate yields in highly productive environments. Inspired by the success of the ‘Chinese miracle’, policy makers and research managers in tropical Asia considered hybrid rice, an innovative technology, as an option to sustain growth in rice production. Rigorous research efforts over the past decade have led to the release of a few promising rice hybrids in India, Bangladesh, Vietnam and the Philippines. This paper aims to assess the prospects for replicating the Chinese miracle of hybrid rice success in other Asian countries, where political systems and other socioeconomic conditions differ from those in China. The authors evaluated farmers' experiences with hybrid rice in India, Bangladesh and Vietnam. The analysis indicates that the particular political system and other socioeconomic factors, and not the inherent economic superiority of this technology, were the driving forces behind the success of Chinese hybrid rice. Thus in other Asian countries, where these factors are not evident and where market forces operate freely (apart from Vietnam), it is unlikely that the success of Chinese hybrid rice will be replicated in toto. Although hybrid rice has a yield gain of about 15–20% over the existing high-yielding modern varieties outside China, it is not attractive to farmers because of higher input costs and lower market prices due to its inferior grain quality. Thus currently available rice hybrids are unlikely to find potential demand in the targeted environments (irrigated rice systems) in the tropics. Hybrid rice would be successful on farms outside China if quality and seed production practices were to be improved and if there was proper deployment planning based on a microlevel analysis of the socioeconomic factors likely to affect its adoption.